Alinhamentos entre economia circular, supply chain management e logística reversa: uma revisão sistemática de literatura - Winck, Bruna (Universidade do Vale do Rio dos Sinos, 2022)
Given the growing importance of the concept of Circular Economy, which can be acknowledged as a possible solution to achieve sustainable development. Its different approaches and different applications, this study aims to identify the link between Circular Economy, Supply Chain Management and Reverse Logistics. This research offers a Systematic Literature Review covering eleven articles published from 2016 to 2021. A conceptual framework containing the definitions of Circular Economy, Supply Chain Management and Reverse Logistics and their alignments is proposed and identified. Additionally, opportunities for future research, such as conducting empirical studies that identify trade-offs associated to Circular Economy in the context of the Supply Chain, the adoption of Blockchain and the consumer perspective are suggested. This study may be useful for both academics and business professionals as it incites further research and guides the integration of the Circular Economy into the Supply Chain.
Keywords: Economia circular; Supply chain management; Logística reversa; Revisão sistemática de literatura; Circular economy; Reverse logistics; Systematic literature review